Properties of moisture resistance kelempayan neolamarckia cadamba based plywood / Mohamad Sukri Mohd Nor Samawi - Mohd Nor Samawi, Mohamad Sukri (Faculty of Applied Sciences, 2016)
The purpose of this study was to evaluate the 3 ply plywood properties which utilize combination of Kelempayan and tropical veneers in term of their physical and mechanical properties. The Kelempayan species veneers used in this experiment were distinguished by two timeline of exposure to the surround environment. Another treatment applied to the plywood was the arrangement of veneer layer. There are three types of veneer arrangement which are the utilization of 100% veneer from Kelempayan, middle ply Kelempayan and middle ply tropical. The plywood process is standardized by using Urea Formaldehyde, hot pressed for 1808, and the glue spread value calculated for relevant surface areas. A test on physical properties on substrate wettability and buffer capacity was conducted prior to bonding. The Kelempayan veneers at 1 month and 3 month exposure pH are not significantly different. The tropical veneers are significantly different with 4.2 ml at P s 0.05. Plywood made was evaluated according to Japanese Agricultural Standard (JAS, 2014) for bending test, tensile test and wood failure test. With regards to veneer age, the new Kelempayan veneer and tropical species is not significantly different, but both of them had significantly higher strength than the old veneer Kelempayan. For arrangement there is a significant difference between the type of plywood arrangement, whereby the best mechanical properties of plywood come from middle ply Kelempayan with modulus of rupture 80.7 MPa and modulus of elasticity 10898 MPa. This experiment suggest to industry to utilize new Kelempayan veneer with a hybrid mix with tropical species veneer as the back and the face for plywood production.